2010
DOI: 10.1182/blood-2009-06-228288
|View full text |Cite
|
Sign up to set email alerts
|

Therapy of B-cell malignancies by anti–HLA-DR humanized monoclonal antibody, IMMU-114, is mediated through hyperactivation of ERK and JNK MAP kinase signaling pathways

Abstract: A humanized IgG4 anti-HLA-DR monoclonal antibody (IMMU-114), engineered to avoid side effects associated with complement activation, was examined for binding and cytotoxicity on leukemia, lymphoma, and multiple myeloma cell lines and chronic lymphocytic leukemia (CLL) patient specimens, followed by evaluation of the effects of IMMU-114 on extracellular signal-regulated kinase (ERK) and c-Jun N-terminal kinase (JNK) signaling pathways. HLA-DR was expressed on the majority of these cells at markedly higher level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
61
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(65 citation statements)
references
References 49 publications
4
61
0
Order By: Relevance
“…Recently, the involvement of ROS was also described in cell death induced by anti-HLA-DR mAbs. 55 Rituximab-induced ROS production was impaired in the presence of EGTA, supporting our hypothesis that Ca 2 þ is important for rituximab-induced ROS. Zhou et al 56 showed that CLL cells with higher basal ROS are more sensitive to 2-Methoxyestradiol, a compound that induces apoptosis via a free radical-mediated mechanism.…”
Section: Discussionsupporting
confidence: 79%
“…Recently, the involvement of ROS was also described in cell death induced by anti-HLA-DR mAbs. 55 Rituximab-induced ROS production was impaired in the presence of EGTA, supporting our hypothesis that Ca 2 þ is important for rituximab-induced ROS. Zhou et al 56 showed that CLL cells with higher basal ROS are more sensitive to 2-Methoxyestradiol, a compound that induces apoptosis via a free radical-mediated mechanism.…”
Section: Discussionsupporting
confidence: 79%
“…Unlike most of other therapeutic monoclonal Ab (mAbs), which exert the in vivo effects largely through immunologic effector mechanisms dependent on intact immunologic function, IMMU-114 acts through direct cytotoxicity, independent of recipient's own immunologic status. Most of mature B cell lymphomas express HLA-DR antigen, making it a potential target for anti-HLA-DR immunotherapy [24,25]. Our current study shows that CLL/SLL express bright HLA-DR and more interestingly that the HLA-DR antigen levels increase over the time of disease course.…”
Section: Discussionmentioning
confidence: 63%
“…Our findings suggest that the rapid and sustained activation of ERKs and JNK may contribute to cell death, 45 as shown in Raji and SU-DHL4 treated with tositumomab and radiation, 46 in renal epithelial cells during oxidative injury, 47 and in Raji and other B-lymphoma lines (including JeKo-1 and Granta-519) on ligation to hL243 (anti-HLA-DR) mAb. 28 We also found that both anti-CD20/CD74 HexAbs disrupt the NF-B pathway by inhibiting the translocation of p65 from cytosol to the nucleus and down-regulate pAkt and Bcl-xL, which may further promote cell death.…”
Section: Discussionmentioning
confidence: 91%
“…On the basis of our previous work on IMMU-114, a humanized anti-HLA-DR mAb 28 and the abundant literature pertaining to the signaling transduction pathways of Abs targeting CD20 (see Vega et al 29 ), we opted to assess the roles of MAP kinases, Src, p65/NF-B, and Akt in Jeko-1 after the colligation of CD74 and CD20. As shown for 74- (20)- (20) and 20-(74)-(74) in the top and middle panels of Figure 6A, both HexAbs induced rapid and sustained activation of ERK and JNK kinases in JeKo-1, which could be detected within 30 minutes, persisted for the next 6 hours, and returned to basal levels by 24 hours.…”
Section: Effect On Map Kinases Src P65/nf-b and Aktmentioning
confidence: 99%